Averaging of the periodic by time boundary value problem for the nonlinear wave equation in a perforated domain - Sidenko, N.R. (Нелинейные граничные задачи, 1999)
In a bounded domain with infinitely increasing quantity of infinitesimal holes whose asymptotic behaviour is described formally, the homogeneous Dirichlet problem for the equation with additional power nonlinearity on the time derivative of the solution is averaged.